EP.TU.369Straight to Test (STT) vs. Traditional Colorectal Target Investigations Pathway - A Local Audit. (28th October 2021) - Fong, Michelle; Shepherd, Sophie; Dixon, Luluwa; Meleagros, Loukis; Dvorkin, Lee; Navaratnam, Romesh
Abstract: Aims: The STT pathway was borne out of the National Cancer Strategy 2015 and faster diagnosis standard to rule in, or out, cancer within 28 days of referral. We aimed to review local target standard of practice, including comparison of STT vs Traditional pathways towards reaching the national standards. Methods: The Somerset Database for all target referrals to the department was accessed. We chose October 2019 as a period unaffected by COVID-19. Time to investigation, results and treatment were reviewed. SPSS v.16 was used to perform an unpaired T-test of Traditional vs. STT time to diagnosis. Results: 212 patients were referred for target investigations. 53 declined, DNA-ed or were unfit. 159 proceeded to investigations of which 7 cancers were diagnosed: 4 colorectal, 1 gastric and 2 lung. Time to diagnosis averaged 45.8 days and only 47/159 (29.6%) had their definitive diagnosis in 28 days. 52 patients were streamed to STT and 107 traditional pathways. STT patients were diagnosed at 36.3 days (95% CI 28.1-44.6) and traditional patients 50.5 days (95% CI 45.4-55.7) (P = 0.005). Cancer treatment was received median day 59 (range 27-189) and 4/7 received this within 62 days. Conclusion: Target investigations have low pick up rates of cancers with ever increasing referrals. Our centre did not meet aspirational national targets of time to treatment or diagnosis, although STT patients were diagnosed significantly faster. With COVID-19, rationalisation of patient contact with maintained diagnosis rates must be strategised. Stricter FIT testing with risk stratification and STT expansion is one strategy.